Essential oils for the treatment of herpes simplex virus infections - Schnitzler, Paul (Chemotherapy, 2019)
Infections with herpes simplex virus type (HSV)-1 and HSV-2 are distributed worldwide. Although standard therapies with acyclovir and other synthetic drugs are available, the safety and efficacy of these drugs are limited due to the development of drug resistance and adverse side effects. The literature on essential oils and isolated compounds was reviewed regarding their antiviral activities against HSV-1 and HSV-2. The present overview aims to review experimental data and clinical trials focusing on the antiviral activity of selected essential oils and isolated oil components. HSV was found to be susceptible to many essential oils and their constituents. Whereas some essential oils and compounds exhibit direct virucidal activity or inhibit intracellular replication, many essential oils and compounds interact with HSV particles thereby inhibiting cell adsorption. Ayclovir-resistant HSV strains are also susceptible to essential oils since their mode of action is different from the synthetic drug. There are numerous publications on the antiherpetic activity of essential oils and their isolated active compounds. This field of research is still growing, and more clinical trials are required to explore the full potential of different essential oils for the topical treatment of herpetic infections.
Gesehen am 10.09.2019